Clinical outcomes of splenorenal shunts in esophageal varices patients: a literature review - Putra, I Gusti Agung Made Adnyana; Hakim, Arief Rakhman; Soebroto, Heroe; Sembiring, Yan Efrata; Limanto, Danang Himawan; Rizki, Mohamad; Puruhito (Indonesian Vascular Access Association (IVAA), 2024)
The disease known as esophageal varices is usually caused by portal hypertension. Portal hypertension is most commonly caused by extrahepatic portal vein thrombosis and other conditions, such as cardiac problems or hepatic cirrhosis. Clinical manifestations of esophageal varices can include melena, haematemesis, and gastrointestinal bleeding. Effective venous pressure reduction is achieved via the distal splenorenal shunt. We acquired the literature for our review from PubMed and Google Scholar. The search was done in English using terms that indicated a connection between improvements in bone grafting methods and the restoration of alveolar clefts. To expand the search results, we also looked through the papers cited in the literature. Almost all of the five gathered articles demonstrated that the distal splenorenal shunt (DSRS) is a beneficial surgical treatment that effectively avoids postoperative PH issues. Finally, DSRS is presented as a surgical long-term treatment for variceal esophageal reflux disease and portal hypertension. Because DSRS selectively decompresses the venous collaterals around the stomach and lower esophagus, it is a safe and effective therapy choice for decreasing bleeding over nonselective shunting surgeries as a selective shunt.